Typhoon-driven Coral-Algal Phase-shifts in Southern Negros Oriental, Philippines - Bucol, Abner A (e-Journal BUDIDAYA PERAIRAN, 2014)
An underwater visual census (UVC) conducted to assess the biophysical conditions of the two marine protected areas (Antulang Marine Protected Area and Andulay Marine Protected Area) in Siaton, Negros Oriental revealed slow recovery from severe damage resulting from Typhoon Sendong in December 2011, suggestive of â€œcoral-algal phase-shiftâ€. Live hard coral (LHC) cover was consistently poor in the survey sites (2.25Â±0.78 % in Antulang Marine Protected Area; 1.25Â±0.50 % in the Control Site; and 3.33Â±0.17 % in Andulay Marine Protected Area) following destruction by the typhoon and colonization of algae (between 37-53%), dominated by Bornetella oligospora. Mean total fish biomass (including fusiliers and schooling juvenile Caranx sexfasciatus) was highest in Antulang Marine Protected Area at 70.60Â±28.07 kg/500m2 (equivalent to 141.21Â±56.14 tonne/km2) while lowest in Andulay Marine Protected Area at 9.83Â±4.32 kg/500m2. Mean total fish density was highest in Antulang Marine Protected Area at 597.0Â±114.7 fish/500m2 followed by the Control Site with 361.7Â±159.0 fish/500 m2, while Andulay Marine Protected Area had 200.7Â±31.6 fish/500m2. Fish species composition was slightly altered, i.e. decline in coral-dependent species such as damselfishes. Keywords: coral reef, macroalgae, phase-shift, resilience, recovery, typhoon